(untitled) (Alternautas, 2022)
The commodity boom and consequent expansion of production has encouraged the emergence of logistical and processing hubs that are functional to the expansion of a commodity production chain and necessary for the extraction of natural resources. It is by creating these corridors designed to reach global markets that the soybean complex has been able to expand and increase its profitability, deepening the extractivist nature of agribusiness in the region. This post looks at the case of the complex of Gran Rosario, an agro-industrial cluster installed on the shores of the Paraná River that has become one of the largest and most efficient hubs for commodity transports in the world, and argues that while usually natural conditions are claimed to be the reasons for its formation, it is a process of concentration of capital and production of space that gives birth to these commodity hubs.